“We may be in the slum, but the slum is not in us!” Zur Kritik kulturalistischer Argumentationen am Beispiel der Underclass-Debatte - Belina, Bernd (ERDKUNDE, 2008)
‘Culture’ is back on the agenda in German geography. Although this development was partly triggered by the import of concepts from Anglo-American ‘new cultural geography’, one of the most important strands of this literature is practically absent from the debate: the contributions of radical geographers grounded in historical-materialist social theory. As a consequence, it is argued that a fundamental critique of the ideological functioning of culturalist argumentations is still missing. The article proposes such a critique in two parts. First, the structure of culturalism is criticized for being both tautological, explaining ‘cultural phenomena’ with ‘culture’, and ideological in that it abstracts from the political nature of social phenomena by treating them as ‘cultural’. The task of a radical cultural geography that follows from this critique is to ask: who argues culturalistically and why? Second, the functioning of the culturalist ideology is illustrated by revisiting the contributions by Murray (1984), Wilson (1987) and Anderson (1999) to the US-American ‘underclass-debate’. All three approaches, it is argued, abstract from the socioeconomic reasons for the existence of Afro-American ghettos in US cities by treating them, in different ways, as ‘cultural’ phenomena. In doing so, all three authors play into the hands, willingly or not, of neoliberal pauperization policies.